Sound Design sebagai Konstruksi Nuansa Mistik: Analisis Sonik dan Resepsi Pendengar terhadap Lagu "Alternate Universe" oleh The Melting Minds - Listyansyah Kartiko Fahmi; Mochammad Usman Wafa (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
This study examines the role of sound design in creating a mystical atmosphere in the song “Alternate Universe” by the independent Yogyakarta band, The Melting Minds. The song adopts an exploratory approach to sonic atmosphere creation through elements such as sub-bass drones, long reverbs, pitch-shifted vocals, and extreme spatial panning. The aim of this research is to identify the sound design techniques used and analyze how listeners interpret their listening experience and how these elements contribute to the emotional experience and mystical perception built by the song. The approach used in this research is a qualitative descriptive-interpretative method, with data collected through audio analysis, documentary observation, semi-structured interviews, and open-ended questionnaires given to 15 experimental music listeners. The theoretical framework includes Schafer’s soundscape theory, Schaeffer’s sound objects, Juslin & Västfjäll's BRECVEMA model of music emotions, and Stuart Hall’s reception theory to understand how listeners interpret their experience. The results show that sound design in this song is used strategically to create a transcendental listening experience, evoking a liminal and affective atmosphere. Techniques such as the use of deep sub-bass drones, extended reverbs, pitch-shifted vocals, and extreme spatial panning were found to be highly effective in shaping a mysterious and profound atmosphere. Listeners reported visualizations of a supernatural space, a floating sensation, and even intense spiritual experiences during the listening.